Characterization of Injection Molded 17-4PH Stainless Steel prepared with Waste Rubber Binder - ABD RAZAK , JEEFFERIE; S., Nurhashima; YAAKOB, MOHD YUHAZRI; Sihombing, Haeryip; S., Mohd Shukor; Abdullah, N.S; Omar, M.A (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2011)
This study is to investigate the sintering characteristics and to establish the best heating rate and soaking time used for sintering process, by determining the physical, mechanical, and microstructural properties of the injection molded 17-4PH stainless steel using waste rubber as a new developed binder system. By using the feedstock which having 65 vol.% of metal powder, the molding are injected into the tensile test bar and immediately processed with two stage debinding process that involves of solvent extraction and thermal pyrolisis to remove the binder. The specimens were sintered at 1360°C under vacuum atmosphere and tested for a critical property analysis of tensile test. Later, the observation on tensile tested specimens fracture surface are done to understand the fracture behavior, distribution of grain and porosity and the significant correlation of fracture morphology to the mechanical properties. From this study, it is found that the combination of 50C/min heating rate and 60 minutes of soaking period resulted in higher density value, higher tensile strength, less porosity and homogenous grains distribution of the sintered specimens.